Effect of alkali and alkaline earth metal ions on benzyl alcohol oxidation activity of titanate nanotube-supported Au catalysts - Nepak, Devadutta; Srinivas, Darbha (RSC Advances, 2015)
Sodium titanate nanotubes (NaTNTs) were prepared by alkali treatment of anatase titania. They were then ion-exchanged with alkali and alkaline earth metal ions to get ATNTs (A = Li+, K+, Cs+, Mg2+, Ca2+, Sr2+ and Ba2+). Gold (1-5 wt%) was supported on these nanotubes by a deposition-precipitation method and investigated as a catalyst for the selective oxidation of benzyl alcohol with air/molecular oxygen (1 atm) under solvent-and alkali-free conditions. Detailed characterization by X-ray powder diffraction, high resolution transmission electron microscopy, N-2-physisorption, diffuse reflectance UV-visible spectroscopy, X-ray photoelectron spectroscopy and CO2-temperature-programmed desorption techniques revealed that the basicity of the catalyst influences the uptake, mean particle size, electronic properties and oxidation activity of the supported gold. Benzaldehyde formed with a selectivity of about 99%. The catalytic activity (turnover frequency) was found to have a direct relationship with the basicity and an inverse relationship with the Au particle size. Among the catalysts investigated, Au/BaTNTs, having higher basicity, smaller Au particles and higher metal dispersion, showed enhanced catalytic activity than the other Au/ATNT catalysts. Pd addition to Au leading to Au-Pd/BaTNTs increased the activity (TOF) but lowered the selectivity for benzaldehyde (80 wt%). Titanate nanotubes donate electron density to Au particles, yielding electron rich Au ions, which are responsible for activating molecular oxygen and oxidizing benzyl alcohol. Au/BaTNTs, having higher basicity and lower size Au nanoparticles than the other Au/ATNT, activates molecular oxygen more easily and thereby enhances the catalytic activity.